Heart Transplantation: 40 Years and Counting - Cindy M. Martin (Methodist DeBakey Cardiovascular Journal)
The field of heart transplantation has experienced remarkable progress over the past decades, transforming from an experimental procedure into a life-saving intervention with continually improving outcomes. As Houston Methodist Hospital celebrates its 40-year milestone in heart transplantation, it is both timely and essential to reflect upon the scientific advancements, ongoing challenges, and emerging opportunities in this dynamic field. Persistent shortages of donor organs, complexities associated with immunosuppressive therapies, and the imperative to optimize long-term patient outcomes continue to drive innovative research and clinical advancements. This issue features a collection of articles exploring key aspects of heart transplantation—from its historical foundations to the latest advances that are shaping its future.